Levels of personality functioning and not depression predict decline of plasma glucose concentration in patients with type 2 diabetes mellitus - Ehrenthal, Johannes C.; Düx, Andreas; Baie, Lara (Diabetes research and clinical practice, 2019)
Aims - Psychosocial variables influence chronic diseases, such as type 2 diabetes mellitus. While there is evidence for a negative impact of depression, much less is known about stable, personality oriented factors. Aim of the study was to assess the impact of depression and personality functioning on glucose regulation in patients with type 2 diabetes. - Methods - Seventy-five adult individuals with a first diagnosis of type 2 diabetes were consecutively recruited in an outpatient medical practice. Plasma glucose (HbA1c) was measured at initial contact, and after three and six months of a standardized disease management program. Depression was assessed by self-report (Patient Health Questionnaire, PHQ-D), levels of personality functioning with the screening version of the Operationalized Psychodynamic Diagnosis structure questionnaire (OPD-SQS). - Results - Using mixed regression models, OPD-SQS scores were associated with lower baseline levels of HbA1c, but a less steep decline over time. PHQ-D scores were neither associated with intercept nor with slopes of HbA1c. - Conclusions - In type 2 diabetes, levels of personality functioning but not depression predicted decline in plasma glucose during the first six months of a standardized disease management program. Personality functioning may be especially important in chronic diseases that demand a high level of compliance and lifestyle change.